EFEKTIVITAS PEMBELAJARAN DARING PADA PROSES PERKULIAHAN MAHASISWA PRODI PENDIDIKAN KEPELATIHAN OLAHRAGA UNIVERSITAS RIAU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research generally aims to determine the effectiveness of online learning in the lecture process of students of the Riau University's sports coaching education study program. The population in this study were students of the Riau University's sports coaching education study program batch 2018, 2019 and 2020. totaling 198 students. The data collection technique used a questionnaire instrument (questionnaire) via google form. The analytical technique used is to pour the frequency into the form of a percentage. The results of this study indicate that the effectiveness of online learning in the lecture process of students of the Riau University sports coaching education study program is said to be good. With consideration. Based on the results of the research and discussion that have been described, it can be concluded that the effectiveness of online learning in the lecture process for students of the Riau University sports coaching education study program is said to be good. Considering the highest frequency is in the "Good" category. This is indicated by the percentage of 64.99% with a sample of 52 active students.Key Words: Effectiveness, Online Learning, Sports Coaching Education